2016
DOI: 10.1007/s00204-016-1793-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor prevents thallium(I)- and thallium(III)-mediated rat pheochromocytoma (PC12) cell apoptosis

Abstract: We have reported recently that the proliferation of PC12 cells exposed to micromolar concentrations of Tl(I) or Tl(III) has different outcomes, depending on the absence (EGF cells) or the presence (EGF cells) of epidermal growth factor (EGF) added to the media. In the current work, we investigated whether EGF supplementation could also modulate the extent of Tl(I)- or Tl(III)-induced cell apoptosis. Tl(I) and Tl(III) (25-100 μM) decreased cell viability in EGF but not in EGF cells. In EGF cells, Tl(I) decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Apoptosis, membrane integrity disruption, MPTP opening, Na + /K + -ATPase inhibition, glutathione depletion, ∆Ψ mito decline, cell viability loss, cytochrome c release, membrane fluidity rise, ATP depletion from mitochondria, and an increase in lipid peroxidation, ROS production, and H 2 O 2 synthesis were induced by Tl + in experiments with isolated rat hepatocytes, isolated synaptosomal mitochondrial fractions of P2, PC12, and HN9.10e neuronal cells, C6 glioma and Jurkat T cells [9,115,[133][134][135][136][137][138][139][140][141][142]. Tl + -induced apoptosis in PC12 cells was later shown to be associated with the activation of the MAPK-dependent cascade of protein kinases: extracellular signal-regulated kinase (ERK)1/2, c-jun N-terminal kinase (JNK), p38, and p53 of the Bcl-2 family [138]. Experiments with TlCl-treated rat hepatocytes found increased cytoplasmic concentrations of Ca 2+ and Na + but decreased K + concentrations [22].…”
Section: Tl(i) Mitochondrial Researchmentioning
confidence: 99%
“…Apoptosis, membrane integrity disruption, MPTP opening, Na + /K + -ATPase inhibition, glutathione depletion, ∆Ψ mito decline, cell viability loss, cytochrome c release, membrane fluidity rise, ATP depletion from mitochondria, and an increase in lipid peroxidation, ROS production, and H 2 O 2 synthesis were induced by Tl + in experiments with isolated rat hepatocytes, isolated synaptosomal mitochondrial fractions of P2, PC12, and HN9.10e neuronal cells, C6 glioma and Jurkat T cells [9,115,[133][134][135][136][137][138][139][140][141][142]. Tl + -induced apoptosis in PC12 cells was later shown to be associated with the activation of the MAPK-dependent cascade of protein kinases: extracellular signal-regulated kinase (ERK)1/2, c-jun N-terminal kinase (JNK), p38, and p53 of the Bcl-2 family [138]. Experiments with TlCl-treated rat hepatocytes found increased cytoplasmic concentrations of Ca 2+ and Na + but decreased K + concentrations [22].…”
Section: Tl(i) Mitochondrial Researchmentioning
confidence: 99%
“…Furthermore, it was discovered that the extent of cell apoptosis induced by Tl (I) and Tl (III) varies in the presence of epidermal growth factor (EGF). The results suggest that EGF partially mitigates toxicity by inhibiting the sustained activation of the MAPK signaling cascade, and indicate that p38 plays a crucial role as a mediator in Tl (III)-induced apoptosis in PC12 cells [64]. Using the HN9.10e cell line, which is a fusion of mouse hippocampal neuroblasts and neuroblastoma cells, it was observed that Tl (I) caused neurite shortening, loss of matrix adhesion, and an increase in cytoplasmic calcium.…”
Section: Mitochondria-mediated Oxidative Stressmentioning
confidence: 94%
“…Geologically, Tl(I) ions are found mostly in potassium-based ores and, when ingested, are handled similarly to K + by ion pumps to living cells. [12,13] Therefore, Tl(I) compounds have median lethal dose of ≥10 mg kg −1 to humans, making them more poisonous than any other Tl(III) compound. [14,15] Coal, smelting, and incineration industry, such as coal-fired power plant facilities, municipal solid waste incineration, nonferrous or ferrous smelting, or hazardous waste combustion, are regarded as the major anthropogenic sources of Tl to the air environment.…”
Section: Introductionmentioning
confidence: 99%
“…Geologically, Tl(I) ions are found mostly in potassium‐based ores and, when ingested, are handled similarly to K + by ion pumps to living cells. [ 12,13 ] Therefore, Tl(I) compounds have median lethal dose of ≥10 mg kg −1 to humans, making them more poisonous than any other Tl(III) compound. [ 14,15 ]…”
Section: Introductionmentioning
confidence: 99%